=G42+G36
=K42-K36
I would like to take the date results from each of the above cells, subtract it from each other and make it appear on a third cell.
I tried this =(G42+G36)-(K42-K36) but it just adds them together.
Thank you
-Joseph
Hello Joseph, welcome to MrExcel
That should work, assuming that the date created from G42+G36 is later than the date created by K42-K36. Make sure that the result cell is formatted as general.
If that still doesn't work then.....what result do you get, exactly. What do you expect?
ADVERTISEMENT
ADVERTISEMENT
If you have those 2 formulas in other cells already, just add the result cells together.
A1=G42+G36
A2=K42-K36
you could use =A1+A2
oops I mean =A1-A2
i'm assuming when you said 'date' in your first post, you actually meant 'data'.
Having said that, i'm seeing some inconsistency in the second formula, as you first said it was
=k42-k36
then went to
g42+g36
in your most recent post
so you tried this formula
=(g42+g36)-(k42-k36)
and got $5.11?
That doesn't make sense if g42+g36 = $2.62 and k42-k36 = $2.49
what's in the 4 source cells?